A Colton internal affair - Bokal, Jennifer D. (Coltons of Grave Gulch., 2021)
"While on patrol, rookie cop Grace Colton pursues a fleeing suspect, never thinking it could end her career--or her life. Suddenly, she's everyone's enemy. Enter Camden Kingsley from Internal Affairs, who rubs Grace the wrong way and seems determined to believe the worst about her. But during interrogations, their sizzling chemistry is obvious, turning foe into unexpected defender, especially as one person desperately wants Grace out of the picture--permanently"--